Optimizing the Performance of SOE Employees in the Banking Sector by minimizing Workload, Burnout, and Job Stress - Nilam Sekar Sari; Arjuna Rizaldi (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
This study aims to excavate and describe the impact of workload, burnout, and job stress on employee performance in state-owned banking companies in the city of Bandung. This research was descriptive and verification methods in nature. The sample used was 60 employees from a total of 150 populations using the Multiple Linear Regression method as an analysis tool. The findings of this study show that all independent variables, namely workload, work weakness, and work stress are described as being in fairly good condition. This shows that the workload, work fatigue, and work stress in the state-owned banking company in Bandung are not in alarming condition. Meanwhile, the dependent variable is employee performance in good condition, which means that even though employees feel workload, work fatigue, and work stress, they are still able to remain productive. In addition, the results of the hypothesis test found that there was a negative and significant influence between the independent variable and the dependent variable. The results of this study are expected to have an impact on controlling workload, work stress, and especially work fatigue, so as to optimize the performance of employees of state-owned banking companies in the city of Bandung.